Structural stability for the Brinkman fluid interfacing with a Darcy fluid in an unbounded domain. (August 2018) - Liu, Yan; Xiao, Shengzhong
Abstract: We study the structural stability for the Brinkman fluid interfacing with a Darcy fluid in an unbounded domain. We show that the solutions depend continuously on the interface coefficient α 1 by using the method of a second order differential inequality. We have never seen any paper deal with the structural stability for the interface fluids in an unbounded domain. Our method would be useful in studying the structural stability for other interface fluid equations in porous media in an unbounded domain.